Educational needs of family caregiver of stroke patients as perceived by the family - Zin, Afiqah Mat (Universiti Sains Malaysia, 2012)
Stroke is one of the important causes of adult disability in many countries. The majority of stroke patients depend on their families for optimum recovery. The objective of the study was to identify the educational needs of family caregivers of stroke patient as perceived by the family. Needs of family caregiver was assessed as preparation for better care for stroke patient. This study was a cross-sectional study and Precede-Proceed model was used in this study. “The stroke caregiver assessment of educational needs survey” was used to measure the educational needs of stroke caregiver at Hospital Universiti Sains Malaysia (HUSM), Kelantan. The survey respondents were 53 family caregivers of stroke patients in ward 2 Intan, 3 Utara, 7 Selatan, and 7 Utara. The result showed that there were 13 topics chosen by stroke family caregiver which showed they needed a lot of education needs. The highest educational need was on “causes of stroke” and “treatment and medication”, with 84.9% respectively. Meanwhile the lowest educational needs was on “how stroke may affect sexual activity” which was only 22.6%. Association between demographic data with “cause of stroke and “treatment and medication” was also identified using chi-square test. The result showed that there was a significant association between “relation with patient” and “causes of stroke”, with p value, 0.002. “Educational level” also showed a significant association with “causes of stroke”, proved by p value, 0.028. Meanwhile, the result showed that there were no significant relationship between “demographic data” with “treatment and medication”. The findings of this study showed that there are a few aspects in educational needs that family caregivers require. Therefore, a comprehensive and effective education needs to be carried out to fulfill their needs.